The Influence of Plafond, Tenor, Application Process, and Loan Frequency on The Growth of Bank Syariah Indonesia's MSMEs Customers - Viantina, Anisa Lia; Purbowisanti, Ratih; Ady Rahmanto, Dhidhin Noer; Ilmiah, Dunyati; Febriyanti, Novi (Institut Agama Islam Negeri Ponorogo, 2022)
Micro, Small, and Medium Enterprises (MSMEs) are essential to economic growth. However, the growth of MSMEs is constrained by difficulties in accessing capital. This study aims to determine the effect of the variable amount of financing (plafond), the application process, the repayment period (tenor), and the frequency of borrowing on the growth of MSMEs. This study uses a quantitative method with a sample of 80 respondents from Bank Syariah Indonesia branch office Sleman Prambanan customers. The sample selection used a purposive sampling technique with the criteria that Bank Syariah Indonesia branch office Sleman Prambanan customers were SMEs in the Yogyakarta and Klaten areas and used financing products such as BSI KUR Micro, BSI KUR Kecil, and BSI Super Micro. The analytical technique used is the classical assumption test, multiple linear regression analysis, t-test, F test, and the coefficient of determination with the help of SPSS software. The results show that the amount of financing (plafond) and the repayment period (tenor) have a positive effect. In contrast, the application process and the borrowing frequency do not positively affect the growth of MSMEs.